Communications in Honduras: the telegraph, the school of telegraphists and the magazine Morse and Bell - Castillo Canelas, Patricia E. (University Magazine, 2022)
Communicating the extensive and desolate Honduran territory was one of the concerns of the different post-independence governments, but the constant lack of national funds and the continuous internal wars made this task difficult. It was during the presidential administration of Marco Aurelio Soto Martínez that, to the extent that public resources allowed, he built the necessary road and communications infrastructure to interconnect the territory and it with the outside world. It is the objective of this work, to publicize the development in the installation of communications in Honduras, the means used to transmit information and leave testimony of how technology left this effective means of communication in oblivion at a given historical moment.